Analisis Pendapatan Usaha Ternak Ayam Ras Petelur di Kota Samarinda - Anindyasari, Dinar; Wibowo, Ari; Haloho, Ruth Dameria (Fakultas Pertanian, Universitas Timor, 2024)
The R/C ratio of laying chickens and the breeders' earnings from rearing laying hens over a year are being researched in this study. This study was carried out in the Lempauke District of Samarinda. Since the laying hen breeding sector is sufficiently large and contains more animals than other industries, a purposeful sample was utilized for the study. The average profit for laying hen farmers in Samarinda is now known to be Rp. 1,378,263,000 for a single period year with a total of 5,000 chickens raised, and the results of the calculation of the level of enterprise efficiency R/C ratio of 2,68 indicate that the Layer chicken Farming in the city of Samarinda is suitable to operate.